Dinamika Pendidikan Pesantren - samsul, arif; Anisah, Anisah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2019)
Pesantren is a form of the normal process of development of the national education system and contains the meaning of authenticity (indigenius) of Indonesia. Along with the times, pesantren have experienced various changes from time to time. Currently the pesantren is in a dilemma position. On the one hand it must preserve its characteristics, on the other hand pesantren have a great responsibility in carrying out the mandate of Islamic da'wah which is always faced with the conditions of the times which are always changing. From time to time pesantren with its elements have experienced many changes to address the various demands that occur in the midst of society. Islamic boarding schools which were originally known as traditional education are now able to survive as an alternative educational institution that educates and continues to exist today and in the future. This writing aims to find and describe the five basic elements of the pesantren and its development, as well as its fundamental values. A qualitative approach with descriptive analysis is an important point to be used as a tool and writing technique. The results show that pesantren always try to respond to the flow of modernization that occurs outside of themselves by taking positive things by developing five basic elements of pesantren without leaving identity as traditional pesantren. At least there are at least five fundamental values ​​that can be taken from the pesantren educational institution, then it can be used as an alternative education that can educate students or students. Includes aspects of tarbiyah / education implementation of lifelong education, ubudiyah / spirituality commitment tafaqquh fi ad-din, khuluqiyah / morality moral service center, ijtima'iyah / pesantren society is a small society and riyadhiyah / entrepreneurship business skills development.